Influence of Product Innovation and Brand Image on the Purchase Decision on CV Cipta Graha Probolinggo - Junaidi; Elmas, M. Syarif Hidayatullah; Dofir, Muhammad; Nabila, Jihan (Formosa Journal of Applied Sciences, 2024)
Product innovation is a process of developing and advancing the quality and quantity of products, With the existence of innovation, the attributed brands will more attract the attention and interest of consumers in determining purchasing decisions. As for the purpose of researchers, it is to know the relationship in product innovation and brand image of purchase decisions on CV Cipta Graha Probolinggo By using a quarantinative approach to liner regression analysis techniques. The sample is based on random sample with a total of 110 respondents. The results of the study found that in the validity of the test reabilitas obtained rtest >rtable, While the value of crobach alpha > 0,60 So variable X1, X2 on the results of the study were reliable. And based on the results ttest It is known that there are partially significant influences of variables X1, X2 (Product inovation and Brand image) of the purchase decision. While on result ftest It was found that the whole variable researched is product innovation and brand image together has a significant effect on the purchase decision CV Cipta Graha Probolinggo.